Design of the ARCHView Augmented Reality Computer Hardware Viewer Application For Software Engineering Learning - Muin, Ni'matullah; Erwin, Erwin; Amanda, Amanda (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2025)
This research aims to design and develop the ARCHView application, an Augmented Reality (AR) Computer Hardware Viewer, intended to support learning in the field of Software Engineering. With advances in AR technology, this application is expected to enhance students' understanding of hardware components through engaging interactive visualizations. The application development process includes 3D modeling of hardware components, integration of AR technology using Vuforia, and the development of interactive features that allow users to interact directly with 3D models. The methodology used in this research includes user requirement analysis, application design, implementation, and functionality testing. Test results show that the ARCHView application can increase student engagement and understanding of the learning material, with 90% of respondents stating that this application is very helpful in the learning process. This research makes a significant contribution to the development of innovative learning methods in the field of Software Engineering, as well as opens up opportunities for further research on the application of AR technology in education.